JURIDICAL ANALYSIS ON THE LEGAL POWER OF COLLATERAL SEIZURE ON MATRIMONIAL JOINT ASSETS IN THE DECISION OF MANNA RELIGIOUS COURT NO. 54/PDT.G/2019/PA.MNA BASED ON ISLAMIC LAW - Fauzi Fauzi; Subanrio Subanrio; Akhmad Muslih (Universitas Bengkulu, 2021)
The objectives of the study were to find out and analyze: (1) the reasons of collateral seizure on matrimonial joint assets where it can guarantee the Plaintiff's rights and (2) The views of Islamic law on the collateral seizure of matrimonial joint assets in the decision of Manna Religious Court No.54/Pdt.g/2019/PA.Mna. This study was normative legal research. The reasons for the seizure of the collateral filed by the Plaintiff in the lawsuit case No.54/Pdt.G/2019/PA.Mna were: a) the reasons for collateral seizure on matrimonial joint assets were due to the Plaintiff’s claim in the lawsuit concerning the assets under the Defendant's authority; b). Judge panel considered the rules based on Al-Qur'an surah An-Nisa verse 32, regulation in Marriage Law, and Compilation of Islamic Law that state the right of Matrimony Joint Assets belongs to both parties, and since the assets were under the Defendant's authority, a collateral seizure is considered necessary; c) the reasons of collateral seizure on matrimonial joint assets were also to provide legal certainty and equal rights to each party; d) to ensure the integrity of the assets, to get them to remain maintained and present; and e) the seizure was to avoid the right transfer of the asset to other parties and to prevent the assets from being misused or damaged. The legal power of collateral seizure of matrimonial joint assets in the decision of Manna Religious Court No.54/Pdt.g/2019/PA.Mna could give the Plaintiff's legal rights in writing, but when viewed from Islamic law it could not be able to achieve the objectives of Islamic law itself, namely the benefit and usefulness principles. This was due to the absence of sanctions and strong foundations for those who did not carry out the decision. The court only granted the seizure stamp and joint assets seizure but did not decide the execution over the joint assets, so the Plaintiff's rights could not be fully protected. Islamic law considered the collateral seizure on matrimonial joint assets in the decision of the Manna Religious Court No.54/Pdt.g/2019/PA.Mna as something that is not prohibited and mentioned in surah Al-Baqarah verse 188.